Exploring factors responsible for absenteeism among undergraduate medical students - Preeti Garg (Wolters Kluwer Medknow Publications, 2023)
Aim: The present study was conducted by for exploring factors responsible for absenteeism among undergraduate medical students. Materials and Methods: After taking students' views on why they thought lectures were important to them, a questionnaire was designed to explore the various factors responsible for absenteeism. Out of 150, 130 students filled the questionnaires and were taken into account for the calculation of data. Also, their recommendations on how to improve class attendance were recorded. All the results were analyzed. Results: Most of the students were of the opinion that lectures are important as they get to interact with teachers and peers, get timely feedback, and develop effective communication skills. The most common reason stated by male students for absenteeism was the long duration of lectures followed by dislike for the teaching style of teachers, while the female students missed classes mainly due to health issues and poor presentation skills of teachers. Conclusion: All these findings call for further research to determine a better understanding of the reasons for absenteeism and its consequences.